RELASI KEKUASAAN ANTARA TIM MANAJERIAL DAN REDAKSI LIPUTAN - Dina Andriana (JIKE: Jurnal Ilmu Komunikasi Efek, 2019)
Power relations reveal hidden things that occur in the Works process between agents in Social practice related to media political economy practices. Media competition requires agents (workers) to compete with innovation and more creatively giving birth to program that are able to attract a large audience. So editors become depressed in producing a program content. Every agents in television media conducts Social practices to channel the relationship between relations which directly or indirectly, or equal or not equal, this indicates the existence of Power. The Research has conducted in the critical paradigma domain, with the Robert K Yin case Study method, where the The of Research was explanatory study regarding the Power relations between manajerial teams and editor Liputan 6 Pagi teams using the theory of Foucault’s Discourse of Power and Knowledge. The Result showed that there were elementer of combination of dominance Power relations and unequal govermentality of Power. Keywords: Power Relations, Foucault, Manajerial Teams, News Program, Editor Teams, Liputan 6 Pagi, SCTV.